Glial Fibrillary Acidic Protein (GFAP) and Cleaved Tau Protein (CTP) Biomarkers as a Forensic Tool for Detection and Assessement of Traumatic Brain Injury - 1 Mohamed Kamel Mohamed1 , Mervat Hamdy Abd Elsalam2 , Eman Abd Elfattah mohammed Elzohairy2 , Dina (Indian Journal of Forensic Medicine & Toxicology, 2021)
Traumatic brain injury (TBI) is defined as a traumatically-induced structural brain injury or physiologicaldisruption of brain function caused by an external force. Traumatic brain injury is a neuropsychiatric disorderthat breaks down the remaining barriers between neurology and psychiatry. Several biomarkers have beendeveloped to directly determine the pathology of the nerve cells in the central nervous system (CNS) whenit is injured. This review recent research on brain injury biomarkers could be used for rapid and accuratediagnostics of TBI in easily accessible fluid.Objectives: The purpose of this study was to assess utility of GFAP-BDP for the diagnosis of intracranialinjury in patients with a positive clinical screen for head injury across the spectrum of TBI typicallypresenting to ED in Kasr- Alainy hospital.Subjects & Methods: This prospective cohort study was based on the data collected from 90 cases presentedto Kasr Al-Aini Hospitals Emergency Department, Cairo University, with history of traumatic brain injurythrough the period from April 2017 to Mars 2019. According to age, they were classified into 3 age groups;age group A (18-35 years), age group B (36-50 years) and age group C (> 50 years). Data were analyzed withrespect to socio-demographic data, type of head injury, clinical presentations, radiological investigation, andmanagement of TBI in relation to serum specific biomarkers level (GFAP, C-tau).Results: The most common age group was age group B (18-35 years) (70%). Males were more commonthan females (71.1% and 28.9% respectively). The most common cause of trauma was fall from height(33.3%). Serum GFAP level and C-tau levels in studied groups show high significant correlation betweenthem (p value <0.001).Conclusion and Recommendations: The combination of the two biomarkers or more may be more usefulthan either biomarker in isolation for predicting intracranial lesions on CT scanning therefor decreasesunwanted CT head scanning and radiological bad effect especially in young ages.